The SmartAG partner: CCAFS East Africa quarterly newsletter, July–September 2013 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In this issue, we highlight emerging opportunities for adaptation planning in Kenya and continuing efforts to strengthen the capacity of African country negotiators to engage in the global climate talks. Read about Kenya’s National Adaptation Planning meeting for the agriculture sector held in mid-September 2013. Through the leadership of CCAFS and key government ministries, a number of stakeholders came together to consider how Kenya should proactively deal with food production challenges and opportunities presented by climate change. We also share with you information about ongoing work with the African Group of Negotiators involved in the United Nations Framework Convention on Climate Change (UNFCC) process. Under science updates, we present ongoing efforts to expand CCAFSs’ Climate Smart Villages (CSV) model implemented through strategic collaboration with a number of partners and how it is helping communities be climate resilient.We provide an example of ongoing research focusing on measurement of greenhouse gases in one of the villages. In the last section; field updates, we present some of the integrated climate smart interventions in practice. These include agroforestry, and livelihood diversification that includes small livestock and knowledge exchange with women farmers engaging in bee farming; among others.